The effect of Bacillus Calmette–Guérin (BCG) vaccination in preventing severe infectious respiratory diseases other than TB: Implications for the COVID-19 pandemic. Issue 41 (22nd September 2020) - Yitbarek, Kiddus; Abraham, Gelila; Girma, Tsinuel; Tilahun, Tizta; Woldie, Mirkuzie
Abstract: The rapid spread of the Coronavirus pandemic and its significant health and social impact urges the search for effective and readily available solutions to mitigate the damages. Thus, evaluating the effectiveness of existing vaccines like Bacillus Calmette–Guérin (BCG) has attracted attention. The aim of this review was e vidence synthesis on the effect of BCG vaccine in preventing severe infectious respiratory disease including COVD-19, but not tuberculosis. We considered studies conducted on human participants of any study design from any country setting that were published in Enlgish. We did a systematic literature search in MEDLINE, Scopus and Google scholar databases and a free search on Google. The identified studies were appraised and relevant data were extracted using Joanna Briggs Institute tools. The extracted findings were synthesized with tables and narrative summary. Nine studies met the inclusion criteria. The findings indicated that BCG vaccine has a strong protective effect against both upper and lower acute respiratory tract infections. For instance in countries with universal BCG vaccination policy, the incidence of COVID-19 was lower compared to the counterparts. Addtionally, BCG vaccine was found to protect against infections like lethal influenza A virus, pandemic influenza (H1N1), and other acute respiratory tract infections. BCG improved the human body's immune response involving antigen-specific T cells and memory cells. It also induced adaptive functional reprogramming of mononuclear phagocytes that induce protective effects against different respiratory infections other than tuberculosis. In countries with universal BCG vaccination, the incidence and death from acute respiratory viral infection including COVID – 19 is significantly low. However, there is an urgent need for further evidence from well-designed studies to understand the possible role of BCG vaccination over time and across age groups, its possible benefits in special populations such as health workers and cost-savings related to a policy of universal BCG vaccination.